2018
DOI: 10.1016/j.ndteint.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of clustered cracks using an ACFM sensor and application of an artificial neural network

Abstract: The alternating current field measurement (ACFM) technique can be applied for surface-breaking fatigue crack detection and sizing; the link between the ACFM signal and crack size is well understood for individual cracks. However, the ACFM response to multiple clustered cracks is significantly different to that of isolated cracks. In railway rails the high wheel-rail forces can lead to rolling contact fatigue (RCF) cracks. Often cracks appear together in small clusters or in long stretches. The accurate charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 52 publications
0
19
1
Order By: Relevance
“…When the workpiece being inspected is a pipe, it is difficult for the probe to induce a uniform current of stable intensity on the surface of the pipe. The commercial ACFM micropencil probe that is manufactured by TSC is used to size the subsurface section of multiple cracks and determine the propagation angle for non-vertical surface-breaking cracks in rail and wheels [10], [20]- [23]. However, the detection range of the micropencil probe is relatively small and the efficiency is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…When the workpiece being inspected is a pipe, it is difficult for the probe to induce a uniform current of stable intensity on the surface of the pipe. The commercial ACFM micropencil probe that is manufactured by TSC is used to size the subsurface section of multiple cracks and determine the propagation angle for non-vertical surface-breaking cracks in rail and wheels [10], [20]- [23]. However, the detection range of the micropencil probe is relatively small and the efficiency is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…A 3D finite element (FE) model was developed using the AC/DC module in COMSOL Multiphysics [17]. This model has been verified previously by experimental measurements for single cracks and uniformly sized crack clusters [4,14,16]. For the modelling work, RCF cracks are assumed to have a semi ellipse shape with elliptical ratios from 1 to 1.75, which has been shown to approximate real (light to moderate) RCF cracks in rails removed from service [3].…”
Section: Model Setupmentioning
confidence: 99%
“…Sizing for crack clusters using an algorithm based on modelling and measurements for single cracks inevitably leads to errors, as shown in [4]. Responses of ACFM Bx signals to various surface lengths, inner spacings and crack numbers for crack clusters have been reported but only cracks with vertical angles of > 30° were considered [16]. Previous studies [14,22] have shown that shallow vertical angles (< 30°) give different Bx signals compared to those obtained for cracks with vertical angles >30° for single and clustered cracks, leading to under estimation of crack pocket lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Leng et al proposed the combined metal magnetic memory (MMM) and the ACFM technique for the detection and evaluation of critical weld joints in a jack-up offshore platform [20]. Rowshandel et al presented the artificial neural network (ANN) for sizing the important subsurface section of the multiple cracks using ACFM [21]. These methods obtained good characteristic signals from the cracks without lift-off variations [22,23].…”
Section: Introductionmentioning
confidence: 99%